Design of palm envo-diesel gas turbine combustion test rig - Ishak, Mohamad Shaiful Ashrul (2012)
Development of gas turbine test rig design need high requirement and specification to successful the project implementation. This paper presented a small scale of test rig using the concept of gas turbine system. Several of pipe size e.g. 6 inch and 12 inch has been fabricated in this project for air supply pipe. The copper igniter with 30kV and using fuel pump integrated with motor was used as a burner to ignite and spray the liquid fuel. Furthermore the axial swirler with 45°angle and 8blades was installed at the center of injector to improve the air swirl. Blower and super heater as a combustion system equipment used to supply and heat an atmospheric air through the piping line. The burner has been fabricated for firing a green and clean fuel for palm envdiesel blends. This characteristic of palm envo-diesel blends will be identifying to meet the requirement of test rig design.